Synthesis and characterization of nanocrystalline cellulose as reinforcement in nitrile butadiene rubber composites - Taib, Mohamad Nurul Azman Mohammad; Yehye, Wageeh Abdulhadi; Julkapli, Nurhidayatullaili Muhd (Editura Academiei Romane, 2020)
In this study, nanocrystalline cellulose (NCC) was produced with different concentrations of hydrochloric acid (HCl) and its surface charge, particle size, crystallinity and thermal properties were assessed. The obtained NCC was then used as reinforcement agent in nitrile butadiene rubber (NBR) composites. The NCC was found to have a particle size less than 100 nm, with surface charge ranging from -0.697 mV to -14.8 mV. The crystallinity index decreased to 64.78% for the NCC obtained with 6M HCl. The NCC synthesized with 1M HCl showed the highest thermal stability, as demonstrated by TGA and DSC results. TEM analysis revealed that the NCC obtained with 5M HCl had the smallest particle size. The addition of different amounts of NCC into nitrile butadiene rubber (NBR) composites led to an enhancement of mechanical properties in terms of tensile strength, modulus and elongation at break up to the loading of 5 phr, but no substantial improvement in tear strength was noticed. © 2020 Editura Academiei Romane. All rights reserved.